Child and Adolescent Mental Health Services in Khartoum State, Sudan: A desktop situational analysis - Abdalhai, Khalid Abdallah (Department of Psychiatry and Mental Health, 2023)
Background Sudan is a Northeast African country, with 61.7% of its population under 24 years. Data concerning child and adolescent mental health (CAMH) is limited in low-income countries. With a large youth population and significant cultural and linguistic diversity, Sudan has contributed minimal data to global CAMH research. Objectives This study aimed to perform a desktop situational analysis of CAMH services in Khartoum state, Sudan. Methods In chapter 1, we performed a literature review of peer-reviewed publications on PubMed and Google scholar and identified relevant articles through search terms relevant to the focus of the study. In chapter 2, we performed a desktop situational analysis of the national capital of Sudan, Khartoum state, in the calendar years 2019 and 2020. The study used the World Health Organization Assessment Instrument for Mental Health Systems version 2.2 adapted for CAMH. The study covered the six WHO-AIMS domains: 1) policy and legislation, 2) CAMH services, 3) CAMH in primary health care, 4) human resources for CAMH, 5) public education, and 6) monitoring and research. Data sources were identified, and relevant information and documents were reviewed. The data were described in tables and figures using the WHO-AIMS version 2.2 template. Ethical approval was obtained from the Human Research Ethics Committee at the Faculty of Health Sciences, University of Cape Town. Results The desktop situational analysis found no available policy legislation specific to CAMH in Khartoum and no separate budget for CAMH. There was no supervising body for CAMH services in Khartoum. Three mental health tertiary hospitals were found to provide services for children and adolescents with mental health problems, all together with adult mental health services. Essential medicines were available in all facilities, except methylphenidate (a stimulant medication used for ADHD), available only in 3 central pharmacies. At the primary care level, there were limited data about training offered to primary healthcare providers and about the process of referral to specialized CAMH services. A School Mental Health Program (SMHP) existed, which provided services for school-aged children and helped in the early identification and management of CAMH problems. The workforce was small and variable across all levels of care. There was no formal public health awareness campaign identified in Khartoum during the study period and little evidence of formal intersectoral collaboration on CAMHS. A health information system existed in Khartoum, but no CAMH-specific items were reported. No national studies in CAMH were identified. Conclusion This situational analysis represented the first systematic collation of data and information about CAMH services in one of the Sudan states. Findings highlighted some areas of strength, but also many gaps in CAMH services and systems. We acknowledge the need to complement the desktop analysis with in-depth data collection with stakeholders across multiple levels, but hope that this will serve as a first step towards strengthening CAMH services in Khartoum and beyond.